Modeling The Types of Online Learning Media Using Multiple Linear Regression Analysis - Isma Muthahharah; Inayanti Fatwa (Universitas Bumigora, 2021)
The research objective is to model the types of learning media Whats App Group, Google Classroom, Zoom and YouTube with multiple linear regression analysis. Multiple linear regression analysis is a linear regression model with one continuous variable and k (two or more) independent variables. This type of research is quantitative research that can model several types of online learning. The object of study in this research is STKIP Pembangunan Indonesia students with a sample of 25 people. The source of data comes from primary data by giving questionnaires to students. Based on the results of the analysis, the type of online learning model obtained is = 70, 376 + 0, 357x1 + 0, 322x2 − 0, 279x1 − 0, 321x2 + ε with a contribution of 21.2%. From the resulting regression model, the best learning models or those often used by Lecturers at STKIP development are WhatsApp Group and Google Classroom. In addition to multiple linear regression analysis, other methods can also be used to model types of online learning media with the addition of media such as LMS Moodle, Edmodo and others.